ChemInform Abstract: Comparative Study of Catalytic Potential of TBAB, BTEAC, and CTAB in One‐Pot Synthesis of 1, 4‐Dihydropyridines under Aqueous Medium. Issue 25 (24th June 2014) - Ananda Kumar, T. Durai; Mohan, P.; Subrahmanyam, C. V. S.; Satyanarayana, K.
Abstract Efficient synthesis of 1, 4‐dihydropyridines via phase‐transfer catalyzed Hantzsch reactions are described.